0123 Simulated multidisciplinary team training in theatre is an effective tool to develop team working skills. (2nd November 2015) - Bamford, Richard; Chinai, Natasha; Evans, Tom; Edwards, Tom; Campbell, Nicola; Hunt, Louise
Abstract : Background: Simulation-based team-working training can improve patient safety and quality of care. We aim to demonstrate how a multi-disciplinary approach to theatre team training can result in improved team working skills. Methods: A multidisciplinary team, simulation based theatre team training programme was introduced within an NHS Foundation Trust. Participants included staff across all disciplines involved in surgical patient care. The team worked through a pre-constructed real time simulated scenarios using SimMan and a laparoscopic box trainer followed by a debrief session. Participants were asked to complete a questionnaire to define their experiences and learning from programme. Results: Twelve participants completed the programme. Time working in the NHS ranged from 3 years to >21 years and 4/12 had never been involved in simulation training before. Ten (10/12 83%) strongly agreed that the programme was a useful for developing team-building skills. 11/12 (92%) agreed (4/12) or strongly agreed (7/12) that the training made them more supportive of their colleagues and listen to others more effectively.83% (10/12) reported better consideration of their colleagues' roles within the theatre team. All participants strongly agreed (5/12) or agreed (7/12) that the training has allowed them to recognise their reaction to stress.92% (11/12) agree of strongly agree that they can now better recognise stress in others and the impact of adverse clinical events.11/12 (92%) reported an increased confidence in identifying potential risks within the operating room and strongly agree (7/12) or agree (5/12) that they are a more effective member of the theatre team. There was no significant difference in the outcome of the survey dependant on time working within the NHS (p = 0.89) or previous involvement in simulation (p = 0.92). Conclusion: Participants valued this simulated multidisciplinary training programme a useful team-training tool in developing key team-working skills regardless of previous experience or exposure to simulation. References: Manser T. Teamwork and patient safety in dynamic domains of healthcare: a review of the literature. Acta Anaesthesiol Scand. 2009;53:143–51 Rabøl LI, Andersen ML, Østergaard D, et al . Descriptions of verbal communication errors between staff. An analysis of 84 root cause analysis-reports from Danish hospitals. BMJ Qual Saf. 2011;20:268–74 Mazzocco K, Petitti DB, Fong KT, et al . Surgical team behaviors and patient outcomes. Am J Surg. 2009;197:678–85 Mardon RE, Khanna K, Sorra J, et al . Exploring relationships between hospital patient safety culture and adverse events. J Patient Saf. 2010;6:226–32